Is Mutans Streptococci count a risk predictor of Early Childhood Caries? A systematic review and meta-analysis - Sheetal Manchanda; Divesh Sardana; Simin Peng; Edward C. M. Lo; Neeta Chandwani; Cynthia K. Y. Yiu (BMC, 2023)
Abstract Background The review aims to determine the risk predictability of mutans streptococci in the development of carious lesions in children with primary dentition. Methods Longitudinal observational studies with at least 6 months follow-up and evaluating mutans streptococci presence in caries-free children under 6 years of age for the development of any cavitated or non-cavitated carious lesion. Six databases and grey literature were searched without any restrictions. Risk of bias was evaluated using the New Castle Ottawa scale for longitudinal studies, and the certainty of the evidence was evaluated by Grading of Recommendations Assessment, Development and Evaluation using GRADEpro software. Meta-analysis was performed using a random effect (DerSimonian and Laird, DL) model, and heterogeneity was evaluated using tau-squared, I2 statistics and prediction interval. Sensitivity analysis was performed to assess the relationship between the mutans streptococci presence at baseline and the caries development, according to the sample and methods used for the microbiological assessment and the length of follow-up of the studies. Publication bias was checked by funnel plot using a random effect (DerSimonian and Laird, DL) model. Results Twelve studies met the inclusion criteria and were included in the review. Four studies received a maximum of 9 stars, and among the remaining eight studies, six received 8 stars and the rest two studies were assigned 7 stars in the risk of bias scale. After pooling the results quantitatively, odds ratio (OR) was found to be 4.13 (95% CI: 3.33, 5.12), suggesting that children with mutans streptococci had 4 times higher odds of developing caries later (p < 0.001). Four studies were pooled to compare future caries experience among children with and without mutans streptococci at baseline, obtaining standardized mean difference (SMD) of 0.85 (95% CI: 0.33, 1.37), indicating a large effect (p < 0.001). Certainty of evidence was found to be moderate, and no publication bias was reported by the funnel plot criteria of symmetry. Conclusions Presence of mutans streptococci in a preschool child is a risk predictor for future caries experience. Early identification of children with increased caries-risk may facilitate in implementation of appropriate preventive strategies.